Adsorption and desorption of nutrients from abattoir wastewater: modelling and comparison of rice, coconut and coffee husk biochar. Issue 11 (November 2021) - Konneh, Morris; Wandera, Simon M.; Murunga, Sylvia I.; Raude, James M.
Abstract: Enrichment of water bodies with nutrients from wastewater is one of the causes of eutrophication to aquatic ecosystems. This study investigated the use of biochar derived from rice husk, coconut husk, and coffee husk in adsorbing nitrates (NO3-N) and nitrites (NO2-N) from slaughterhouse wastewater. It also explored the desorption efficiencies of the adsorbed nutrients to ascertain the applicability of the enriched biochars as slow-release fertilizers. To characterize the physicochemical properties of the biochars, scanning electron microscopy (SEM) was used. Fourier transforms infrared spectroscopy (FTIR), elemental analysis (CHNO) Langmuir and Freundlich, and the isotherm models were employed to fit the experimental equilibrium adsorption data. It was observed that the Langmuir isotherm model has the best fit of NO3- N and NO2- N on all the biochars. And this was based on the coefficient of correlation values. Also, the coconut husk biochar has the highest adsorption capacities of NO3-N and NO2-N at 12.97 mg/g, and 0.244 mg/g, respectively, attributing to its high porosity as revealed by the SEM images. The adsorption capacities for the rice husk char were 12.315 and 0.233 mg/g, while that for coffee husk char were12.08 mg/g and 0.218 mg/g for NO3-N and NO2-N, respectively. The relatively higher amount of NO3-N adsorbed to that of NO2-N could be attributed to its higher initial concentration in the solution than nitrite concentration. The desorption efficiencies of nitrates were 22.4, 24.39, and 16.79 %, for rice husk char, coconut husk char and coffee husk char, respectively. For the rice husk char, coconut husk char and coffee husk char, the nitrites desorption efficiencies were 80.73, 91.39, and 83.62 %, respectively. These values are good indicators that the studied biochar can be enriched with NO3- N and NO2- N and used as slow-release fertilizers. Abstract : Biochar; Adsorption; Desorption; Langmuir; Freundlich; Nitrates; Nitrites; Slaughterhouse.